2013
DOI: 10.3171/2013.6.jns122099
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the difference in posterior circulation involvement between pediatric and adult patients with moyamoya disease

Abstract: Object. There is no description of the change in the posterior cerebral artery (PCA) in the diagnostic criteria of moyamoya disease (MMD). However, PCAs are often involved in the clinical setting, and an understanding of the significance of PCA lesions is therefore of great importance when evaluating the disease progression and predicting prognosis. The aim of this study was to assess the difference in posterior circulation involvement in pediatric and adult patients with MMD.Methods. The records of 120 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 14 publications
(20 reference statements)
5
43
1
Order By: Relevance
“…It is noteworthy that steno‐occlusions were not restricted to the anterior circulation. The PCA was affected in 26.5% of our adult MMD patients which is comparable to recently published Asian data . However, Caucasian pediatric patients showed a remarkably higher PCA steno‐occlusion compared to adults (60% vs. 26.5%, respectively).…”
Section: Discussionsupporting
confidence: 88%
“…It is noteworthy that steno‐occlusions were not restricted to the anterior circulation. The PCA was affected in 26.5% of our adult MMD patients which is comparable to recently published Asian data . However, Caucasian pediatric patients showed a remarkably higher PCA steno‐occlusion compared to adults (60% vs. 26.5%, respectively).…”
Section: Discussionsupporting
confidence: 88%
“…Third, we have chosen the Suzuki staging system to classify the severity of MMD, 27,28 but it has been reported that this system was based mainly on intensified serial angiographic changes or decreases in moyamoya vessels, and clear disadvantages remain in the accuracy of classification based on angiographic findings. 29,30 Therefore, the staging system defined by Mugikura et al 30 should be used for precise staging in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Even when steno‐occlusive involvement of the PCA was not included in the diagnostic criteria for MMD, many studies reported posterior circulation involvement in patients with MMD. However, PCA involvement has been related to a higher frequency of infarction in children with MMD (Hishikawa, Tokunaga, Sugiu, & Date, ). Among our patients, we observed seven PCA involvements (19%) in six patients.…”
Section: Discussionmentioning
confidence: 99%